Financial Performance as a Mediator of GCG, Firm Size, and Firm Value - Ibrahim Ibrahim; Indira Oktavianti (Universitas Budi Luhur, 2026)
This study analyzes the effects of Good Corporate Governance (GCG) and firm size on firm value, as well as the mediating role of financial performance, in mining companies listed on the Indonesia Stock Exchange (IDX) for 2022-2024. Research variables are managerial ownership, indpendent board of commissioners, firm size, financial performance (ROA), and firm value. The sample was 16 companies, yielding 48 observations. Data was analyzed using a Fixed-Effects Model (FEM) panel regression in Eviews 12. Results showed managerial ownership significantly affectd firm performance. The independent board of commissioners and firm size were not significant. Financial performance had a negative effect. Mediation analysis showed that financial performance mediated the link between managerial ownership and firm value. This confirms that managerial effectiveness and profitability drive firm value. This confirms that managerial effectiveness and profitability drive firm value, while ownership structure and company scale have limites influence on investor persceptions.